Genetic diversity in yardlongbean (Vigna unguiculata subspecies unguiculata cvgr sesquipedalis) as revealed by simple sequence repeat (SSR) markers - Ogunkanmi, L.A.; Ogundipe, O.T.; Ng, N.Q.; Scoles, G.J.; Fatokun, C.A. (2007)
Genetic diversity was investigated among fifty accessions of yard-long-bean (Vigna unguiculatasubspecies unguiculatacultivar group sesquipedalis) using simple sequence repeat (SSR) markers. Sixteen SSR primers were used to amplify DNA of the 50 accessions. A total of 63 polymorphic bands were detected and these were used for cluster analysis. A dendrogram generated following unweighted pair group using mathematical average (UPGMA) cluster analysis isolated one of the accessions from the others at a similarity coefficient of 0.68. However, at 0.76 similarity coefficient, nine clusters were formed with the eighth and ninth clusters containing more than two-thirds of the total accessions used. There were four accessions that paired at 1.0 similarity coefficient. The members of each pair could not be separated from each other on the dendrogram suggesting very close relationships be-tween each pair. The distribution of the yard-long-bean accessions along the axes of the first two principal components showed to a very large extent similar grouping as were identified on the den-drogram. Accessions of yard-long-bean from India showed the highest level of genetic diversity, as revealed by SSR markers, compared with those from other countries thereby providing further evidence in support of the suggestion that India may be the center of diversity for the crop. Thus SSR markers are useful in assessing the genetic diversity among individuals of yard-long-bean.